Influence of quenching and tempering heat treatment on heat flux to the workpiece in dry milling of AISI 1045 steel - Nícolas Pinheiro Ramos; Mariana de Melo Antunes; Antonio Augusto Araújo Pinto da Silva; Gilmar Guimarães; Sandro Metrevelle Marcondes de Lima e Silva (Case Studies in Thermal Engineering)
Dry machining offers cost and environmental benefits in metal cutting, but the absence of cutting fluid can elevate workpiece temperature, impacting surface quality and dimensional accuracy. This study explores and quantifies the impact of quenching and tempering heat treatment on the heat flux to the work material in dry milling AISI 1045 steel. Inverse heat transfer analysis determines the maximum magnitude of a moving Gaussian heat source corresponding to the heat load into the milled part. The inverse estimates are obtained from temperature measurements taken when machining samples subject to different heat treatment conditions. The estimated heat flux and the measured temperature are discussed in the context of the metallo-thermomechanical connection with microstructural aspects, hardness, and thermal properties. The results reveal a substantial increase in thermal energy transferred to the milled steel when quenched and tempered, with a 33 % higher heat input compared to normalized conditions. This condition is mainly attributed to the increased hardness and reduced thermal conductivity of the tempered martensitic structure obtained through hardening. The estimates show deviations of less than ±5 %, according to uncertainty calculations based on thermal sensitivity and sensor accuracy.